The C-reactive protein/albumin ratio predicts postoperative delirium in patients older than 60 years following total knee arthroplasty - Zhang, Lin; Li, Baoquan; Bai, Yujiang; Liu, Xiaoshuang; Chai, Xin (Frontiers in Surgery, 2022)
Purpose: This study aimed to investigate the relationship between serum C-reactive protein (CRP) /Albumin ratio (CAR) and postoperative delirium (POD) in patients older than 60 years following total knee arthroplasty (TKA). Methods: From January 2019 to January 2021, 268 patients were recruited in this prospective observational investigation. Patients with serum CRP, Alb, CAR, delirious status and delirious score were assessed. The effect of CRP, Alb, CAR on predicting delirium was assessed with the area under the receiver operating characteristic (ROC) curve (AUC). Results: The study found that higher CRP level (P < 0.001), low Alb level (P < 0.001), and higher CAR (P < 0.001) were independently associated with POD. The AUC of CAR for POD was 0.782, with the cut-off value of 0.117, a sensitivity of 83.3% and a specificity of 65.9% respectively (P < 0.001), suggesting that CAR had moderate efficacy on predicting POD occurrence than CRP (AUC: 0.761) and Alb (AUC: 0.300). The results also showed that age, ASA and the operation time was an independent predictor for patients with POD. Conclusions: Our findings demonstrated CAR may be an effective biomarker to predict postoperative delirium in patients over 60 years of age with TKA, which provides potential recommendations for early intervention in delirium care. Keywords: delirium; CRP; Alb; TKA; biomarker.